Problematika Kebijakan Peningkatan Kualitas Guru: Antara Sertifikat dan Realitas di Lapangan - Abdul Rosyid; Sahrul Romansah; Sari, Diana Ratna; Masduki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher certification policy is one of the government’s strategic instruments to improve teacher professionalism, the quality of learning, and the overall standard of national education. Normatively, teacher certification is intended to provide formal recognition to teachers as professional educators who possess pedagogical, professional, social, and personal competencies. However, the reality in practice indicates that possession of a teaching certificate does not always correlate with improvements in learning quality. This article aims to analyze the challenges of teacher quality improvement policies, particularly the gap between certification and the realities of educational implementation at the school level. This study employs a qualitative approach using a literature review method. The context of the study focuses on UPTD SMPN Satu Atap 2 Gantar, Indramayu Regency, which is characterized as a small school with 3 permanent teachers, 3 non-permanent teachers, and 54 students. The analytical framework is based on George C. Edward III’s policy implementation theory, which includes aspects of communication, resources, disposition, and bureaucratic structure. The findings reveal that teacher certification has not been optimal as an instrument for improving quality due to the dominance of administrative orientation, limited resources, weak post-certification development, teacher workload, and the lack of a strong reflective and collaborative culture within schools. Therefore, certification needs to be integrated with continuous professional development, humanistic academic supervision, teacher learning communities, and impact-based evaluation of learning outcomes to ensure that teacher quality improvement policies become more meaningful and contextual.